Full-Mouth Rehabilitation Using All-Ceramic Restorations - Luvizuto, Eloá R [UNESP]; Queiroz, Thallita P. [UNESP]; Betoni-Júnior, Walter [UNESP]; Sonoda, Celso Koogi [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Castro, José Carlos Monteiro de [UNESP]; Boeck, Eloisa M. [UNESP] (My University, 2015)
The scientific and technological advancement of cosmetic dentistry has improved metal-free ceramic systems for fixed prosthodontics as well as porcelain veneers, making them an excellent treatment option for delivering superior cosmetic results. The authors present a clinical case of full-mouth rehabilitation using all-ceramic restorations with porcelain metal-free unit crowns in the maxilla, and porcelain veneers from the left inferior premolar to the right inferior premolar. Using this approach, they were able to achieve an excellent esthetic and functional result for the patient.